Selecting Best Venue for MICE and Policy Implication in Indonesia - Nining Yuniati, Nining Yuniati (Rumah Jurnal UNEJ, 2025)
Indonesia already has standards in the development of MICE destinations which are a reference for districts/cities, namely Regulation of the Minister of Tourism Number 5 of 2017. In this regulation there are four variables which have a number of comprehensive indicators which are the requirements for how to create ideal MICE tourist destinations. However, before this regulation was released, many empirical studies had been carried out by world researchers which resulted in several criteria which were then included in existing policies in Indonesia. Using the semi-systematic review method, it can be underlined that in general the number of studies conducted can be grouped into four variables, namely 1) Services including accessibility, HR, and all forms of services 2) Facilities such as accommodation and convention facilities 3) Amenities of supporting facilities such as shopping centers, banking services, and tourist information 4) Attractions, which consist of interesting places, entertainment, recreation, and tourist attractions. These four things later became the fundamental basis for the development of MICE destinations in Indonesia as mandated by the Minister of Tourism Regulation No. 5 Year 2017